تقنيات الحوار في رواية " ثائر من الجزائر" للكاتب عبد القادر قسيمة - هركوس ,اكرام; بركة عبد ,العزيز; بن مصباح ,فارس (University of Eloued جامعة الوادي, 2024)
لقد تطرقنا في دراستنا لتقنية الحوار لغة واصطلاحا، وخصايته ومميزاته عن المصطلحات المشابهة له، كالجدال،المفاوضة،المناظرة، والمناقشة. ومن هنا تعرضنا لأنواع الحوار بجميع أشكاله(الحوار الخارجي، الحوار الداخلي، الحوار الوصفي، الحوار التأثيري) وعلاقة التداخل بين الحوار والسرد الذي به يقوم الحوار، وارتكزنا عاى بعض النقاط الذي تميز السرد وأهم الآليات الذي يقوم عليه السرد. وفي الأخير الدراسة التطبيقة للحوار عن رواية«ثائر من الجزائر» لعبد القادر قسيمة الذي قسمنا فيها أنواع الحوار للرواية. ثم علاقة الأمير مع مختلف الشخصيات في الرواية ثم الرسم الذي زاد الرواية رونقة وجمال لتعدده في جميع أنحاء الرواية الذي أكد على أحداث الرواية. In our study, we touched upon the technique of dialogue, language and terminology, its specificity and advantages over similar terms, such as argument, negotiation, debate, and discussion. Hence, we were exposed to the types of dialogue in all its forms(external dialogue, internal dialogue, descriptive dialogue, influential dialogue) and the relationship of overlap between the dialogue and the narrative in which the dialogue is based, and we focused on some points that distinguish the narrative and the most important mechanisms on which the narrative is based. Finally, the Applied study of the dialogue on the novel"A Rebel from Algeria" by Abdelkader koussima, in which we divided the types of dialogue for the novel. Then the Prince's relationship with the various characters in the novel, and then the drawing that increased the novel's elegance and beauty for its multiplicity throughout the novel, which emphasized the events of the novel.
نقد ومناهج
Keywords: الحوار، السرد، الرواية، الأمير عبد القادر، الرسم; dialogue; narrative; novel; Prince Abdulkader; painting